Development of bicycle shift models in Universiti Kebangsaan Malaysia campus - Amiruddin Ismail,; Shazrizil Zakaria, (Fakulti Kejuruteraan ,UKM,Bangi., 2014)
Cycling is suitable for short trips and take shorter commute time for students who are living in the campus. Moreover, it requires lower costs and can reduce environmental pollution. However, cycling in campus is not well received by the students. This is due to certain factors such as hilly terrain, uncertain weather, and also the exposure to road traffi c accidents. A survey had been conducted in UKM Bangi campus to identify the factors that can infl uence students to choose cycling as the main choice of transport. Surveys were targeted to 170 respondents from the students in the campus. Two bicycle shift models were developed based on travel distance of non-hilly terrain and travel distance if covered lane provided. 76.5% of the respondent agreed that hilly terrain makes bicycle is not an option inside campus while 79.4% believe that the weather condition makes them not to choose bicycle. From both model, it is seen that the probability to shift to bicycle is increased as the travel distance increases if the terrain is not hilly and if there is covered lane provided. Overall, the study is a success and might be useful for future research on sustainable transportation system in campus.